2022
DOI: 10.3389/fbioe.2022.962040
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial cells during craniofacial development: Populating and patterning the head

Abstract: Major organs and tissues require close association with the vasculature during development and for later function. Blood vessels are essential for efficient gas exchange and for providing metabolic sustenance to individual cells, with endothelial cells forming the basic unit of this complex vascular framework. Recent research has revealed novel roles for endothelial cells in mediating tissue morphogenesis and differentiation during development, providing an instructive role to shape the tissues as they form. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…After formation, neural crest cells undergo a process known as the epithelial-to-mesenchymal transition, during which they detach from the uppermost part of the neural tube. 49 Recent studies 50 , 51 have revealed that endothelial cells and the vasculature play a pivotal role in guiding tissue morphogenesis and cell differentiation in various cranial structures. Additionally, genes from the vascular endothelial growth factor (VEGF) family have been observed in the mesenchyme surrounding Meckel’s cartilage.…”
Section: Resultsmentioning
confidence: 99%
“…After formation, neural crest cells undergo a process known as the epithelial-to-mesenchymal transition, during which they detach from the uppermost part of the neural tube. 49 Recent studies 50 , 51 have revealed that endothelial cells and the vasculature play a pivotal role in guiding tissue morphogenesis and cell differentiation in various cranial structures. Additionally, genes from the vascular endothelial growth factor (VEGF) family have been observed in the mesenchyme surrounding Meckel’s cartilage.…”
Section: Resultsmentioning
confidence: 99%
“…the lamina propria) also contains the vasculature of the TM ( Mozaffari et al, 2020 ). The timing of the invasion of the vasculature was followed in Mesp1cre;tdTomato mice, where Mesp1 drives tdTomato expression in mesodermal derivatives, including endothelial cells ( Asrar and Tucker, 2022 ). In unperforated TMs, blood vessels were observed around the annulus and the manubrium, while the centre of the PT was devoid of vasculature ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…5 ). For this, CD31 was used to label endothelial cells ( Asrar and Tucker, 2022 ) and Wnt1cre;tdTomato to label the mesenchymal cells of the lamina propria. At 5 dpp ( Fig.…”
Section: Resultsmentioning
confidence: 99%